Subjective wellbeing impacts of national and subnational fiscal policies - Arthur Grimes; Judd Ormsby; Anna Robinson; Siu Yuat Wong (REGION, 2016)
We study the association between fiscal policy and subjective wellbeing using fiscal data on 34 countries across 129 country-years, combined with over 170,000 people's subjective wellbeing scores. While past research has found that "distortionary taxes" (e.g. income taxes) are associated with slow growth relative to "non-distortionary" taxes (GST/VAT), we find that distortionary taxes are associated with higher levels of subjective wellbeing than non-distortionary taxes. This relationship holds when we control for macro-economic variables and country fixed effects. If this relationship is causal, it would offer an explanation as to why governments pursue these policies that harm economic growth. We find that richer people's subjective wellbeing is less harmed by indirect taxes than people with lower incomes, while "unproductive expenditure" is associated with higher wellbeing for the middle class relative to others, possibly reflecting middle class capture. We see little evidence for differential effects of fiscal policy on people living in different sized settlements. Devolving a portion of expenditure to subnational government is associated with higher subjective wellbeing but devolving tax collection to subnational government is associated with monotonically lower subjective wellbeing.
Keywords: D60; E62; H50; H70; O57; 330; Subjective wellbeing; Fiscal policy; Decentralised government